Meta analysis of learning models in improving Higher Order Thinking Skills (HOTS) in junior highs school mathematics learning - Khasanah, Uswatun; Hidayah, Isti (Unnes Journal of Mathematics Education, 2022)
The Industrial Revolution 4.0 requires students to have Higher Order Thinking Skills (HOTS). To achieve this aim, an effective learning models is needed with various cosiderations. Many studies have been conductes and provide different conclusions, so that new problems arise regarding which learning models is considered more influential in improving students’ HOTS. This study aims to find, compared, and analyzed learning models that have been used in improved HOTS at the junior high school level. The method used being narrative meta-analysis. The subjects of this study were 2 (two) articles that met inclusion criteria and had passed the PRISMA procedure. The result showed that the effect size values for each group of Project Based Learning (PjBL) assisted by Geogebra, Challenges Based Learning (CBL) and Problem Based Learning (PBL) were 3.27, 2.25, and 1.09. This shows that PjBL assisted by Geogebra have a greater influence than other learning models because the synrax of the learning model applied and the learning media used.